2009
DOI: 10.1128/cvi.00211-09
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Mycobacterium bovis Antigens by Dissection of Crude Protein Fractions

Abstract: Culture filtrate and cell extracts from Mycobacterium bovis cultures contain molecules which could promote protective immunity to tuberculosis in animals. Different protein fractions of M. bovis cultures were obtained by elution electrophoresis and were tested in experimentally infected cattle. The fractions that elicited gamma interferon (IFN-␥) responses were resolved by two-dimensional gel electrophoresis, and individual proteins were identified by matrix-assisted laser desorption ionization-time of flight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 38 publications
3
14
0
Order By: Relevance
“…On the other hand, PE5 is a member of the PE family that is present in the mycobacterial cell wall, and is considered, along with TB10.4 and PE13, to be an antigen that is sensitive and highly specific in the IFN-γ assay (Aagaard et al 2006). Although Mb0143 was also considered a satisfactory antigen in IFN-γ assay to identify experimentally infected cattle (Meikle et al 2009), its sensitivity levels were not satisfactory in the skin test.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, PE5 is a member of the PE family that is present in the mycobacterial cell wall, and is considered, along with TB10.4 and PE13, to be an antigen that is sensitive and highly specific in the IFN-γ assay (Aagaard et al 2006). Although Mb0143 was also considered a satisfactory antigen in IFN-γ assay to identify experimentally infected cattle (Meikle et al 2009), its sensitivity levels were not satisfactory in the skin test.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, proteins, such as EsxI (Jones et al 2010), Mb0143, PE5, PE13 and TB10.4 previously assessed in IFN-γ assays (Aagaard et al 2006, Meikle et al 2009, were evaluated in skin test in cattle. Excluding TB10.4, which was recently evaluated in skin test in cattle by Xin et al (2013), all the other proteins were assessed for the first time in skin test in bovines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with ELISA these results have shown that random mutagenesis and shortening the linker can improve the binding characteristics of chicken scFvs. Since the 16 kDa TB protein is known to be a useful diagnostic target for serodiagnosis and cellular immunoassays [5,6], the engineered scFvs described here are likely to be useful research tools and in diagnostics development.…”
Section: Discussionmentioning
confidence: 99%
“…This antigen is considered to be a potentially useful diagnostic target for serodiagnosis of TB in humans [5] and can also be used to stimulate lymphocytes in the gamma interferon test for bovine TB [6]. Antibodies directed against this protein are therefore likely to be useful in research and diagnosis.…”
Section: Introductionmentioning
confidence: 99%